Factors Influencing Tourist Attitudes Toward Environmentally Friendly Practices in Four-Star Hotels in Garut - M Faza Fauzan Adhima (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to identify and analyze the factors that influence tourist attitudes toward environmentally friendly practices in four-star hotels in Garut. The research employs a quantitative approach using Confirmatory Factor Analysis (CFA) to validate the measurement model based on five latent constructs: environmental concern, personal norms, perceived value, willingness to pay, and green purchasing behaviour. Data were collected through a structured online questionnaire distributed to 100 respondents who had previously stayed in four-star hotels in Garut. The questionnaire items were adapted from previous studies and measured using a five-point Likert scale. The analysis confirmed that the observed variables grouped into three key dimensions that influence tourist attitudes, namely: green awareness and responsibility, perceived economic value, and green action tendencies. These results suggest that internal awareness, perceived benefits, and behavioral orientation play a critical role in shaping tourist support for green practices in the hospitality industry. The study provides practical insights for hotel managers to improve communication strategies, enhance sustainable facility offerings, and design guest participation programs that align with tourist values. This research highlights the importance of aligning environmental initiatives with guest expectations to increase acceptance and active involvement in sustainable tourism.